Pathway to lamellar bodies for surfactant protein A - Fisher, Aron B. (American Physiological Society, 2010)
Alveolar surfactant protein A (SP-A) is endocytosed by type II epithelial cells through clathrin-dependent uptake and targeted to lamellar bodies for resecretion. However, the mechanism for secretion of newly synthesized SP-A, whether regulated exocytosis of lamellar bodies or constitutive secretion, is unresolved. If it is the latter, lamellar body SP-A would represent endocytosed protein. Amantadine, an inhibitor of clathrin-coated vesicle budding, was used to evaluate the role of endocytosis in accumulation of SP-A in lamellar bodies. In isolated rat lungs, amantadine (10 mM) inhibited uptake of endotracheally instilled (35)S-labeled biosynthesized surfactant proteins by >80%. To study trafficking of newly synthesized SP-A, lungs were perfused for up to 6 h with [(35)S]methionine, and surfactant was isolated from lung lavage fluid and lamellar bodies were isolated from lung homogenate. With control lungs, the mean specific activity of [(35)S]SP-A (disintegrations per minute per microgram of SP-A) increased linearly with time of perfusion: it was significantly higher in isolated lamellar bodies than in surfactant and was increased in both compartments by 50–60% in the presence of 0.1 mM 8-bromo-cAMP. These results suggest a precursor-product relationship between lamellar body and extracellular [(35)S]SP-A. Specific activities in both compartments were unaffected by addition of amantadine (10 mM) to the lung perfusate, indicating that uptake from the alveolar space was not responsible for the increase in lamellar body [(35)S]SP-A. Thus the pathway for secretion of newly synthesized SP-A is by transfer from the site of synthesis to the storage/secretory organelle prior to lamellar body exocytosis.